2009
DOI: 10.1111/j.1365-3156.2008.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Case fatality of SARS in mainland China and associated risk factors

Abstract: Summary Objective To analyse the case fatality ratio (CFR) and its risk factors for severe acute respiratory syndrome (SARS) in mainland China by using a comprehensive dataset of all probable cases. Methods The data of all probable SARS cases were derived from the Infectious Disease Reporting System of the Center of Diseases Control and Hospital Information Systems, during the 2003 epidemic in mainland China. The definition of probable SARS case was consistent with the definition for clinically confirmed SARS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 15 publications
2
63
1
Order By: Relevance
“…However, the relatively young ages of the cases (median age 33 years) only partly (approximately 25%) explains the low CFR in mainland China compared with other affected areas and countries, where patient median age varied from 37 years in Singapore to 49 years in Canada (Table 1). 18 The relatively lower proportion of hospital-acquired infections in mainland China (reflected in the lower proportion of infections among HCWs compared with other areas [19% vs. 23%-56%; see Table 1]) is also only partly responsible for the lower CFR in mainland China, especially since this factor is highly correlated with age.…”
Section: Case Fatalitymentioning
confidence: 99%
“…However, the relatively young ages of the cases (median age 33 years) only partly (approximately 25%) explains the low CFR in mainland China compared with other affected areas and countries, where patient median age varied from 37 years in Singapore to 49 years in Canada (Table 1). 18 The relatively lower proportion of hospital-acquired infections in mainland China (reflected in the lower proportion of infections among HCWs compared with other areas [19% vs. 23%-56%; see Table 1]) is also only partly responsible for the lower CFR in mainland China, especially since this factor is highly correlated with age.…”
Section: Case Fatalitymentioning
confidence: 99%
“…125 It caused severe lower respiratory tract infection with a severe morbidity and a high case-fatality rate (approaching 50% in individuals over 60 years of age, overall 10%). 63,106,107,126 Person-toperson transmission of SARS-CoV is well established. 55 The virus has spread to 29 countries and has been estimated to have caused more than 8000 infections and 774 deaths worldwide (Table 1).…”
Section: Sars-cov and Mers-covmentioning
confidence: 99%
“…Serology (not in acute phase) [100][101][102] Serology (not in acute phase) 103 Case-fatality rate in adults Sporadic cases reported in immunosuppressed adults 104,105 6%-17% 63,66,106,107 20%-40% 67 SARS-CoV-2 is currently estimated at 2.7. 38 The incubation period is estimated at 5-6 days, which is similar to that for SARS-CoV and MERS-CoV.…”
Section: Unknownmentioning
confidence: 99%
“…Moreover, for the H5N1 and pandemic H1N1 cases, elder cases of >60-year-old were significantly fewer than expected (both covering <5% of the total cases), and young cases of <40-year-old, especially for those of 019-year-old, were significantly higher than expected, both covering >80% of the total cases [6,7]. Figure 1 also showed that the age distribution of H7N9 cases was similar to the SARS outbreak in 2003 in China in that the group of 019-year-old were significantly fewer than expected, but different from the SARS outbreak in that elder cases of >60-year-old were significantly fewer than expected for the SARS outbreak [4].…”
Section: Clinical and Demographic Characteristics Of The First 91 Casesmentioning
confidence: 70%
“…Among them, 88.37% (76/86) developed severe and acute respiratory symptoms including pneumonia, and 17 had died. The case fatality rate was approximately 18.68%, sig-nificantly higher than that of the SARS outbreak in China in 2003 (6.44%) [4]. From the data of 13 fatalities of known relevant data, the interval between the occurrence of symptoms and death of the fatal cases was 12.22 (mean)  6.76 d (standard deviation).…”
Section: Clinical and Demographic Characteristics Of The First 91 Casesmentioning
confidence: 84%